Legal Issues in the Implementation of Excise Tariffs on Cigarette Companies in Madura - Aziz, Warit (Faculty of Law Universitas Trunojoyo Madura, 2024)
Cigarette excise rates are relatively expensive and not affordable by consumers (people) with middle to lower income, resulting in the large circulation of illegal cigarettes without excise. The legal problems that need to be studied are the regulation of illicit cigarettes without excise in Madura, the implementation of these arrangements for the people of Madura, which has led to the proliferation of illegal cigarettes, and the effectiveness of policies against illegal cigarettes without excise. This research uses empirical legal research with socio-legal and anthropological approaches. The research and study results show that, First, unaffordable excise tariffs cause the rampant circulation of illegal cigarettes without excise, so based on the theory of the